A Case Report of Acute Severe Necrotizing Pancreatitis following the Johnson & Johnson Vaccine against the Novel SARS-CoV-2. (22nd March 2023) - Bangolo, Ayrton I.; Akhter, Mahabuba; Auda, Auda; Akram, Rahina; Nagesh, Vignesh K.; Athem, Donnee; Thomas, Reenu; Tibalan, Ligaya; Trivedi, Mansi; Mushtaq, Saima; Singh, Neha; Bagale, Pracheta; et al.
Abstract : Acute pancreatitis is an inflammatory condition, which is a leading gastrointestinal cause of hospitalization in the United States. Several conditions are associated with acute pancreatitis. More recently, there have been a few cases reported of acute pancreatitis following the Pfizer-BioNTech COVID-19 mRNA vaccine. To our knowledge, no cases of acute pancreatitis have been yet reported following the Johnson & Johnson's Janssen COVID-19 vaccine (J& J vaccine). Herein we report a 34-year-old male with no significant past medical history admitted with acute necrotizing pancreatitis, the day following the receipt of the J&J vaccine. Based on the Naranjo and the modified Naranjo scale, the patient met the requirements for probable drug induced pancreatitis. This case report has the objective to raise awareness of a potentially severe side effect of the J&J vaccine. We hope to use this case to support screening all patients for previous history of acute pancreatitis before administration of the J& J vaccine.